Adenosine Diphosphate Improves Wound Healing in Diabetic Mice Through P2Y12 Receptor Activation - Borges, Paula Alvarenga; Waclawiak, Ingrid; Georgii, Janaína Lima; Fraga-Junior, Vanderlei da Silva; Barros, Janaína Figueiredo; Lemos, Felipe Simões; Russo-Abrahão, Thaís; Saraiva, Elvira Maria; Takiya, Christina M.; Coutinho-Silva, Robson; Penido, Carmen; Mermelstein, Claudia; et al. (Frontiers in Immunology, 2021)
Chronic wounds are a public health problem worldwide, especially those related to diabe-tes. Besides being an enormous burden to patients, it challenges wound care professionals and causes a great financial cost to health system. Considering the absence of effective treatments for chronic wounds, our aim was to better understand the pathophysiology of tissue repair in diabetes in order to find alternative strategies to accelerate wound healing. Nucleotides have been described as extracellular signaling molecules in different inflam-matory processes, including tissue repair. Adenosine-5’-diphosphate (ADP) plays im-portant roles in vascular and cellular response and is immediately released after tissue in-jury, mainly from platelets. However, despite the well described effect on platelet aggrega-tion during inflammation and injury, little is known about the role of ADP on the multiple steps of tissue repair, particularly in skin wounds. Therefore, we used the full-thickness excisional wound model to evaluate the effect of local ADP application in wounds of dia-betic mice. ADP accelerated cutaneous wound healing, improved new tissue formation, and increased both collagen deposition and transforming growth factor-β (TGF-β) pro-duction in the wound. These effects were mediated by P2Y12 receptor activation since they were inhibited by Clopidogrel (Clop) treatment, a P2Y12 receptor antagonist. Fur-thermore, P2Y1 receptor antagonist also blocked ADP-induced wound closure until day 7, suggesting its involvement early in repair process. Interestingly, ADP treatment in-creased the expression of P2Y12 and P2Y1 receptors in the wound. In parallel, ADP re-duced reactive oxygen species (ROS) formation and tumor necrosis factor-𝛼 (TNF-𝛼) levels, while increased IL-13 levels in the skin. Also, ADP increased the counts of neu-trophils, eosinophils, mast cells, and gamma delta (γδ) T cells (Vγ4+ and Vγ5+ cells sub-types of γδ+ T cells), although reduced regulatory T (Tregs) cells in the lesion. In accord-ance, ADP increased fibroblast proliferation and migration, myofibroblast differentiation, and keratinocyte proliferation. In conclusion, we provide strong evidence that ADP acts as a pro-resolution mediator in diabetes-associated skin wounds and is a promising inter-vention target for this worldwide problem.